2003
DOI: 10.1002/jcp.10209
|View full text |Cite
|
Sign up to set email alerts
|

Chemical sympathectomy‐induced changes in TH‐, VIP‐, and CGRP‐immunoreactive fibers in the rat mandible periosteum: Influence on bone resorption

Abstract: The expression of neurotransmitter receptors by bone cells supports the concept that the nervous system is a regulator of bone metabolism. The discrimination of the respective roles of the sensory and sympathetic nervous systems requires evidence of topographic relationships between the corresponding fibers and the cells involved in bone turnover, in vivo. In this study, the influence of the sympathetic system on bone resorption was assessed by using a synchronized model of cortical resorption along the mandib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 43 publications
1
53
0
Order By: Relevance
“…Moreover, nerve fiber distribution has been shown to change in response to neurological injury. Induced sensory and sympathetic denervation dramatically alters the distribution of immunoreactive fibers within rat bone [21,46]. Neurological injury may result in physiological changes within the bone microenvironment, including shunt formation in blood circulation and changes in cytokine or neuro-osteotrophic factor expression, that ultimately lead to osteoclast activation and osteoblast inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, nerve fiber distribution has been shown to change in response to neurological injury. Induced sensory and sympathetic denervation dramatically alters the distribution of immunoreactive fibers within rat bone [21,46]. Neurological injury may result in physiological changes within the bone microenvironment, including shunt formation in blood circulation and changes in cytokine or neuro-osteotrophic factor expression, that ultimately lead to osteoclast activation and osteoblast inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Bone is densely innervated, and the observation of direct contact of nerve fibers and bone cells strongly supports a role of innervation in bone cell functions. A number of neuromediators have also been detected by immunocytochemistry in nerve fibers in bone [18][19][20][21][22][23]. These studies suggest an important role of the neural system in regulating bone cell functions, and ultimately in influencing bone homeostasis.…”
Section: Introductionmentioning
confidence: 85%
“…The recruitment of the monocytes reaches a maximum level 12 hours after induction and is complete 24 hours after induction; osteoclastic resorption follows the recruitment of the monocyte and peaks 4 days after induction. 7,18 Rats were locally treated by injecting histamine (4 l of a solution at 10 g/ml), mast cell degranulating agent c48/80 (4 l of a solution at 100 g/ml) or saline (vehicle, VEH) close to the site of resorption 19 8 hours after activation. Other rats were treated systemically with intramuscular injection of saline H1R antagonist mepyramine solution (1.5 mg/kg/day), saline H2R antagonist famotidine solution (10 mg/kg/day) or VEH, either beginning immediately after extractions (early treatment) or 24 hours later, ie, after inflammatory cell recruitment (delayed treatment).…”
Section: In Vivo Experimental Designmentioning
confidence: 99%
“…Likewise, chemical sympathectomy of neonatal rats treated with guanethidine increases resorption in the mandibular bone surface [Hill et al, 1991]. In contrast, when guanethidine is administered to adult rats, the number of mononuclear pre-osteoclast(s), tartrate-resistant acid phosphatase-positive (TRAPþ) cells [Cherruau et al, 1999], as well as bone resorption pits [Cherruau et al, 2003], are reduced in the mandibular cortex subjected to synchronized resorption by molar(s) extraction. Other authors [Haug and Heyeraas, 2003], using a similar experimental model, found that surgical sympathectomy increases osteoclastic activity in the mandible, but not in the maxilla suggesting a site-specific response of bones to sympathectomy.…”
mentioning
confidence: 95%